Seeds of Violence: How Fanaticism and Exclusivism in Early Childhood Religious Education Shape Intolerant Dispositions - Muliono Muliono; Dinda Syufradian Putra; Hapsa Hapsa; Aditya Romadhon; Arwansyah Kirin (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
This study aims to reveal and analysis the potency of violent values in early childhood education that is taught through religious teaching materials. This study is critical to analyze because the understanding of violence instilled in childhood can have long-lasting effects on their social and mental development such as fostering aggressive behavior, normalizing violence, and causing social maladjustment. This study uses a qualitative method. And, to reveal the forms of potential violence through the teachings being taught, this study is also supported by questionnaire data. The findings in this study show that two types of religious teachings have the potential as seeds of violence internalized in kindergarten namely exclusivism and fanaticism. These two types represent characteristics of theological claims that exert consequences in shaping the understanding of intolerant motivations and behaviors. By using the genealogy of power theory as knife analysis, this study concludes that the potency of violence based on religious values in early childhood education does not only reflect how the power operates systematically within religious teachings in a micro context in the form of teacher-student relationships in generating violence understanding but also reflects a broader context within social and political structures.